2021
DOI: 10.1111/ina.12930
|View full text |Cite
|
Sign up to set email alerts
|

Airborne SARS‐CoV‐2 surveillance in hospital environment using high‐flowrate air samplers and its comparison to surface sampling

Abstract: Reliable methods to detect the presence of SARS‐CoV‐2 at venues where people gather are essential for epidemiological surveillance to guide public policy. Communal screening of air in a highly crowded space has the potential to provide early warning on the presence and potential transmission of SARS‐CoV‐2 as suggested by studies early in the epidemic. As hospitals and public facilities apply varying degrees of restrictions and regulations, it is important to provide multiple methodological options to enable en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 34 publications
0
39
1
Order By: Relevance
“…Although there was no appreciable difference in the sensitivity of IP2 and IP4, our results underline that it is necessary to include several markers to increase the chance of getting a signal, especially when expected results are close to the limit of the assays’ performance. The LoD in our study was 2.2 virus copies per liter of air, which is higher than some other SARS‐CoV‐2 air studies 34,35 . Many studies do not report LoD in terms of viral concentration in air, but the lowest reported values across several SARS‐CoV‐2 air sampling studies indicate large differences in LoD 36 …”
Section: Discussioncontrasting
confidence: 62%
“…Although there was no appreciable difference in the sensitivity of IP2 and IP4, our results underline that it is necessary to include several markers to increase the chance of getting a signal, especially when expected results are close to the limit of the assays’ performance. The LoD in our study was 2.2 virus copies per liter of air, which is higher than some other SARS‐CoV‐2 air studies 34,35 . Many studies do not report LoD in terms of viral concentration in air, but the lowest reported values across several SARS‐CoV‐2 air sampling studies indicate large differences in LoD 36 …”
Section: Discussioncontrasting
confidence: 62%
“…The dose d was estimated by. where N resp is the total number of respirations (20 times per minute), V tidal is the tidal volume (500 ml per respiration), λ is the average viable rate of the virus based on previous field studies ( Ang et al, 2022 , Dumont-Leblond et al, 2020 , Lednicky et al, 2020a , Lednicky et al, 2020b , Lednicky et al, 2021 ; Nannu Shankar et al, 2022 , Xie et al, 2020 ), listed in SI. 1 Table.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, surveillance of virus-laden aerosols is suitable for monitoring this path and assessing qualitative and quantitative molecular epidemiological information on population exposure to SARS-CoV-2 ( Anand et al 2021 ). So far, many studies have detected the presence of SARS-CoV-2 RNA in indoor aerosols, mainly in hospitals ( Ang et al, 2022 , Baboli et al, 2021 , Barbieri et al, 2021 , Bazzazpour et al, 2021 , Cheng et al, 2020 , Chia et al, 2020 , Ding et al, 2021 , Dumont-Leblond et al, 2020 , Feng et al, 2021 , Ghaffari et al, 2021 , Guo et al, 2020 , Habibi et al, 2021 , Hemati et al, 2021 , Kenarkoohi et al, 2020 , Lednicky et al, 2020a , Lednicky et al, 2020b ; Liu et al, 2020 , Lopez et al, 2021 , Nor et al, 2021 , Passos et al, 2021 , Razzini et al, 2020 , Stern et al, 2021a , Stern et al, 2021b ; Tan et al, 2020 , Yarahmadi et al, 2021 , Zhou et al, 2021 ), as well as in residential rooms ( Nannu Shankar et al 2022 ), transportation ( Hadei et al, 2021 , Lednicky et al, 2021 , Moreno et al, 2021 ) and other public indoor places ( Hadei et al 2021 ). Some further detected the presence of SARS-CoV-2 nucleocapsids ( Krambrich et al 2021 ) or even viable viruses ( Lednicky et al, 2020a , Lednicky et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The primary risk factors for transmission include the community incidence of a given viral pathogen (since this determines the probability of any given healthcare worker or patient may be a carrier), respiratory viral load (higher viral loads are associated with higher rates of transmission), 65,66 severity of symptoms (patients with more severe symptoms emit more respiratory particles of all sizes), 67 proximity of exposure (the viral plume is most concentrated right next to the source but rapidly dissipates and dilutes with distance), 68,69 duration of exposure (longer exposure periods are associated with greater cumulative exposure), 69 quality of ventilation (good ventilation dilutes viral emissions, poor ventilation allows for the accumulation of virusladen aerosols leading to more exposure), 70,71 and, where available, vaccination (vaccines decrease both the probability and duration of viral carriage). 72,73 Aerosol-Generating Procedures One factor that does not appear to substantially increase transmission risk is so-called "aerosol-generating procedures".…”
Section: Risk Factors For Transmissionmentioning
confidence: 99%